2016
DOI: 10.1007/s12026-016-8797-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-1 family cytokines single nucleotide polymorphisms with susceptibility to systemic sclerosis: an independent case–control study and a meta-analysis

Abstract: The aim of our study was to investigate the association of five single nucleotide polymorphisms in interleukin-1 (IL-1) gene with susceptibility to systemic sclerosis (SSc) in a Chinese population. A total of 58 SSc patients and 113 healthy controls were enrolled. TaqMan allele discrimination assay was performed to detect the genotyping of IL-1A -889C/T (rs1800587), IL-1B -511C/T (rs16944), IL-18 -607C/A (rs1946518), IL-18 -137G/C (rs187238) and IL-33 rs7044343. The association between these SNPs and SSc risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The human IL-1α (IL-1A) gene contains common SNPs including rs1800587 and rs17561, which have been reported to be linked to several autoimmune diseases in some populations. IL-1A rs1800587 was reported to be associated with SSc susceptibility in the Slovak Caucasian, Japanese, and Chinese populations (1315). However, this association was not supported by other relevant studies (16).…”
Section: The Association Of Il-1 Family Genes and Sscmentioning
confidence: 99%
See 1 more Smart Citation
“…The human IL-1α (IL-1A) gene contains common SNPs including rs1800587 and rs17561, which have been reported to be linked to several autoimmune diseases in some populations. IL-1A rs1800587 was reported to be associated with SSc susceptibility in the Slovak Caucasian, Japanese, and Chinese populations (1315). However, this association was not supported by other relevant studies (16).…”
Section: The Association Of Il-1 Family Genes and Sscmentioning
confidence: 99%
“…Results showed that IL-18 rs187238 and IL-18 rs1946518 polymorphism were not correlated with SSc susceptibility. However, ESR and dyspnea were associated with IL-18 rs187238 and IL-18 rs1946518 polymorphism, respectively (13).…”
Section: The Association Of Il-1 Family Genes and Sscmentioning
confidence: 99%
“…Genome-wide association studies have revealed associations between genes encoding IL-1 family cytokines and SSc. The human IL-1α (IL-1A) gene contains the sodium nitroprusside (SNP) rs1800587, which has been reported to be associated with SSc susceptibility in the Slovak Caucasian, Japanese, and Chinese populations [ 127 ]. However, in a very recent meta-analysis, IL-1A rs1800587 polymorphism seems not to be statistically linked to the risk of SSc [ 128 ].…”
Section: The Expression and Function Of Nuclear Alarmins Hmgb-1 Imentioning
confidence: 99%
“…Genetic polymorphisms in the IL-33 gene may be useful for the prediction of the risk of various diseases. The IL-33 rs7044343 CC genotype was suggested to be associated with an increased risk of developing SSc and a decreased risk of developing RA; the T allele may be a susceptibility marker for premature coronary artery disease and central obesity and possibly involved in the regulation of IL-33 production ( 53 , 75 77 ). The first monoclonal anti-ST2 antibody, CNTO-7160, was recently designed as a new IL-33 inhibitor; this antibody is being evaluated in phase I clinical trials for the treatment of severe asthma and atopic dermatitis, but no data have been published to date ( 78 ).…”
Section: Clinical Applications Of Il-33 In Sscmentioning
confidence: 99%